2005
DOI: 10.1002/ajmg.b.30114
|View full text |Cite
|
Sign up to set email alerts
|

Genome screen for loci influencing age at onset and rate of decline in late onset Alzheimer's disease

Abstract: We performed an affected sib-pair (ASP) linkage analysis to test for the effects of age at onset (AAO), rate of decline (ROD), and Apolipoprotein E (APOE) genotype on linkage to late-onset Alzheimer's disease (AD) in a sample comprising 428 sib-pairs. We observed linkage of mean AAO to chromosome 21 in the whole sample (max LOD = 2.57). This came entirely from the NIMH sample (max LOD = 3.62), and was strongest in pairs with high mean AAO (>80). A similar effect was observed on chromosome 2q in the NIMH sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
57
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 36 publications
19
57
3
Order By: Relevance
“…We did not find evidence for linkage for GSTO1 at 10q26.12 for the age-at-onset phenotype, but found weak evidence for linkage with the AD phenotype [21]. Holmans et al [13] performed an affected sib-pair linkage analysis with ageat-onset, and observed the strongest support for linkage at chromosome 21q21, which was previously reported by Olson and colleagues [16]. In our dataset, locus 21q22 yielded a modest LOD score of 1.08.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We did not find evidence for linkage for GSTO1 at 10q26.12 for the age-at-onset phenotype, but found weak evidence for linkage with the AD phenotype [21]. Holmans et al [13] performed an affected sib-pair linkage analysis with ageat-onset, and observed the strongest support for linkage at chromosome 21q21, which was previously reported by Olson and colleagues [16]. In our dataset, locus 21q22 yielded a modest LOD score of 1.08.…”
Section: Discussionsupporting
confidence: 65%
“…With few exceptions [13,16], reports of genome-wide scans of familial AD have relied on the clinical diagnosis as the trait of interest [5]. However, Li et al [14,40] argued that the age-atonset of disease is equally important because the "regulation of onset could make it possible to delay onset beyond an individual's normal life span."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach is to include suspected sources of heterogeneity as covariates in the statistical model. The use of covariates in linkage analysis has contributed to mapping or confirming the position of genes for prostate cancer, 8,9 late-onset Alzheimer disease 10,11 and recurrent early-onset depression. 12 In this study, we report the results of a sibling pair linkage analysis of CAD on chromosome 2 using the British Heart Foundation (BHF) Family Heart Study including hypercholesterolemia as a covariate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous genome-wide family-based linkage analyses have identified several loci linked to AD [9][10][11][12][13][14][15][16][17][18][19] and confirmed linkage by several groups has been reported to chromosome (chr.) 9p, 9q, 10q, 12p and 19q.…”
Section: Introductionmentioning
confidence: 57%